2016
DOI: 10.19071/jaa.2016.v2.3000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen, shading and intercropping on alfalfa-ziziphus agroforestry system under arid land conditions

Abstract: <p>To assess the arid lands agroforestry potential, a field experiment was performed at the Agricultural Research Station of King Abdulaziz University, located at Hada Al-Sham during the 2013 and 2014 seasons. Alfalfa was evaluated in a <em>Ziziphus</em> agroforestry system at a distance of 1 m, 2 m and 4 m from the ziziphus tree and were supplied with three different levels of nitrogen fertilizer 0 kg/ha, 200 kg/ha and 400 kg/ha in the form of commercial Urea. The fertilizer were subdivided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Alfalfa is a nitrogen-fixing plant, which lives in a symbiotic relationship with the nitrogen-fixing bacteria-the rhizobia-which lives in nodules in the plant's roots [32]. The results indicated that intercropping alfalfa with ziziphus and walnut trees can effectively increase the nitrogen content in the soil and biomass of plants [33,34]. However, it is easy to form a soil barrier with karst soil to hinder the acquisition of phosphorus by plants because of its high calcium content and pH [35].…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa is a nitrogen-fixing plant, which lives in a symbiotic relationship with the nitrogen-fixing bacteria-the rhizobia-which lives in nodules in the plant's roots [32]. The results indicated that intercropping alfalfa with ziziphus and walnut trees can effectively increase the nitrogen content in the soil and biomass of plants [33,34]. However, it is easy to form a soil barrier with karst soil to hinder the acquisition of phosphorus by plants because of its high calcium content and pH [35].…”
Section: Introductionmentioning
confidence: 99%